Ethnic representation and stereotypes in mathematics and Dutch language textbooks from the Netherlands - van Veen, Daudi; Emmen, Rosanneke A. G.; van de Rozenberg, Tessa M.; Mesman, Judi (Whiteness and education (Print), 2024)
The current study examined ethnic representation and stereotypes in textbooks from two core secondary school subjects: maths and Dutch. We examined all 25 hard-copy textbooks used in first-year secondary schools in the Netherlands in 2019, and coded characters' ethnic background, competence-related activities, and occupational status. Ethnicity was identifiable for 8897 characters. Results indicate that characters of colour were underrepresented in the text and images in the textbooks compared to Dutch population statistics. Additionally, subtle stereotypical patterns were found in which characters of colour were less competent and lower in occupational status than White characters. These findings suggest that implicit biases influence which groups are featured and how they are portrayed. To help all students to reach their full potential and develop an inclusive worldview, we recommend publishers use publicly available tools (e.g. random name generators) to make their textbooks more inclusive.